La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Black Women Dancers, Jazz Culture, and “Show Biz”: Recentering Afro-Culture and Reclaiming Dancing Black Bodies in Montréal, 1920s–1950s - Jabouin, Emilie (Canadian Journal of History, 2021)
The documentary Show Girls, directed by Meilan Lam, makes an unprecedented contribution to the history of jazz and Black women jazz dancers in Montréal, Quebec, and to the conversation of jazz in Canada. Show Girls offers a glimpse into the lives of three Black women dancers of the 1920s–1950s. This essay asks what the lives of Black women dancers were like and how they navigated their career paths in terms of social and economic opportunities and barriers. I seek to better understand three points: (1) the gap in the study of jazz that generally excludes and/or separates dance and singing from the music; (2) the use of dance as a way to commercialize, sell, and give visual and conceptual meaning to jazz; (3) the importance of the Black body and the role of what I would define as “Afro- culture” in producing the ingenious and creative genre of jazz. My study suggests there is a dominant narrative of jazz, at least in academic literature, that celebrates one dimension of jazz as it was advertised in show business, and that bringing in additional components of jazz provides a counternarrative, but also a restorative, whole and more authentic story of jazz and its origins. More specifically, by re- exploring jazz as a whole culture that relies on music, song, and dance, this essay explores three major ideas. First, Black women dancers played a significant role in the success of jazz shows. Second, they articulated stories of self, freedom, and the identity of the New Negro through jazz culture and dance. Third, Black women’s bodies and art were later crystallized into images that further served to sell jazz as a product of show business.

Dick Montgomery et la personnification féminine afrodescendante en Amérique du Nord, 1935-1960 - Jacques, Raphaël (Histoire Engagée, 2021)

Black Gold: A Black Feminist Art History of 1920s Montréal - Joachim, Joana (Canadian Journal of History, 2021)
The 1920s have been touted as the golden era of jazz and Black history in Montréal. Similarly, the decade is well known for the Harlem Renaissance, a key moment in African American art history. Yet this period in Black Canadian art histories remains largely unknown. As a first step toward shedding some light on this period in Black Canadian art history, I propose to use what I term a Black feminist art-historical (bfah) praxis to discuss some visual art practices undoubtedly active alongside well-known jazz musicians and cultural producers in 1920s Montréal. This paper presents an overview of critical race art history and feminist art history, as well as Black feminist approaches to visual representation, to outline what might be considered four tenets of bfah praxis. Applying these tenets, I propose that a new art history may emerge from well-known art objects and practices as well as lesser-known ones. I posit that through a deliberately bfah approach, new meanings emerge and the voices of Black women, even when obstructed by mainstream white narratives, may begin to stand out and shed light upon a variety of histories. This praxis aims to underline the subtext lurking at the edges of these images and to make intangible presences visible in the archive and in art history. I propose bfah as a strategy for more nuanced discussion of the work of Black Canadian artists and histories that have by and large been left out of official records.